«Pasa la vida»: Cartografías Urbanas de Madrid en la Post-Transición (1982-1994) - Vicente Rodríguez Ortega (Cahiers de Civilisation Espagnole Contemporaine)
This essay analyzes representations of the everyday in the Madrid cityscape from the beginning of the 1980s until the mid 1990s. During the Transition, Spanish cinema started to explore forms of interaction that negotiated recently born stimuli and social, economic and ideological formations, displaying as strong commitment to the representation of social reality and, more specifically, the marginalized. From the late 1980s to the mid 1990s, filmmakers tackle a social fabric characterized by a «presentism» that leaves behind a productive commitment to recent Spanish history and the capacity of the citizenry to decisively intervene within the constitutive pillars of social reality. In the studied period, Spanish cinema encounters an ever-flowing social, approaching it from different perspectives, turning into a representational mechanism that codifies the practices of the everyday –that is, the recurrent forms of interaction through which individuals function with a given social structure.